POLYCARBONATE RESIN COMPOSITION AND MOLDED PRODUCT COMPRISING THE SAME - NAGATA KOSUKE (2024)
To provide: a polycarbonate resin composition having excellent rigidity, electromagnetic shielding characteristics and thermal shock resistance; and a molded product comprising the same.SOLUTION: A polycarbonate resin composition comprises: (A) 100 pts.wt. of a polycarbonate resin (A component); (B) 5-100 pts.wt. of carbon fibers (B component); (C) 0.001-1 wt.pt. of at least one phosphate ester (C component) selected from the group consisting of phosphonic acid esters (C-1 component) having acid values of 0.01-0.30 mg KOH/g and acid phosphate esters (C-2 component) having acid values of 10-200 mg KOH/g; and (D) 0.05-10 pts.wt. of a compound (D component) which obstructs adhesion between the A component and B component.SELECTED DRAWING: None 【課題】剛性、電磁遮蔽特性および耐熱衝撃性に優れたポリカーボネート樹脂組成物をおよびそれからなる成形体を提供する。【解決手段】（Ａ）ポリカーボネート樹脂（Ａ成分）１００重量部に対し、（Ｂ）炭素繊維（Ｂ成分）を５～１００重量部、（Ｃ）酸価が０．０１～０．３０ｍｇＫＯＨ／ｇであるホスホン酸エステル（Ｃ－１成分）および酸価が１０～２００ｍｇＫＯＨ／ｇである酸性リン酸エステル（Ｃ－２成分）よりなる群より選ばれる少なくとも１種のリン酸エステル（Ｃ成分）を０．００１～１重量部および（Ｄ）Ａ成分とＢ成分との密着性を阻害する化合物（Ｄ成分）を０．０５～１０重量部含有するポリカーボネート樹脂組成物。【選択図】なし